ANALISA SATUAN BAHAN PEKERJAAN BEKISTING BETON BERTULANG: STUDI KASUS PADA PEKERJAAN BANGUNAN GEDUNG - Suhendra Suhendra (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
Formworks in the reinforced concrete building work usually use wood as the material. The wood made as board or beam with specified dimension. The aim of the research is to calculate the volume of wood using as formwork in the building-work. The volume of wood as formwork calculate by assume the using of formwork are as well as the concrete made. Therefore, the repetition of using formwork ignored.The result shown the coefficients of formwork volume are different significantly from the coefficient supplied in the unit-work analysis. The difference will take effect to the whole cost of the building work, consequently will lead to the offer-cost estimate of the executants (i.e. building contractor).Keywords: formwork, unit-work analysis, reinforced concrete